Influence of Perceived Price, Product Quality, and Brand Image on Purchase Decisions on the TikTok Application with Customer Trust as a Mediating Variable in Bengkulu City - Pratama, Bayu Abdi; Hayu, Rina Suthia (Student Journal of Business and Management, 2024)
The purpose of this study is to examine the effect of Perceived Price, product quality and brand image mediated by Customer Trust in the Tik Tok application in the city of Bengkulu. The sampling technique in this study used a purposive sampling technique. The data collection technique used a questionnaire which was distributed online through social media. Measurement research in this questionnaire consists of 17 questions to respondents. The number of samples is 160. The analysis tool used is PLS-SEM with the help of the SmartPls program version 3.2.9. The results show that (1) Perceived Price has a positive effect on Customer Trust; (2) the quality of product has a positive effect on Customer Trust; (3) brand image has a positive effect on Customer Trust; (4) Perceived Price has a positive effect on purchase decision; (5) the quality of product has a positive effect on purchase decisions; (6) brand image influences purchase decision; (7) Customer Trust influences purchase decision; (8) Customer Trust mediates the effect of Perceived Price on purchase decision; (9) Customer Trust mediates the effect of product quality on purchase decisions; (10) Customer Trust mediates the effect of brand image on purchase decision